Teacher’s Strategies in English Vocabulary Instruction for Learners with Hearing Impairment at Special Education School - Sarlan Hamid; Sri Agriyanti Mestari; Haris Danial (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to explore teacher’s strategies in English vocabulary instruction for learners with hearing impairment at SLB Negeri Kota Gorontalo. It employed a descriptive qualitative design to gain an in-depth understanding of classroom practices in a natural setting. Data were collected through classroom observations and semi-structured interviews with an English teacher experienced in teaching learners with hearing impairment. The findings reveal five main strategies: (1) sign language, (2) visual media, (3) fingerspelling, (4) lip reading, and (5) drilling strategy. Sign language is the most dominant, serving as the primary medium to bridge students’ understanding of English vocabulary. Visual media, such as pictures and flashcards, support comprehension, while fingerspelling helps students recognize word structures. Lip reading facilitates pronunciation and articulation, and drilling strengthens memory through repetition. Therefore, more interactive, multimodal, and technology supported strategies are recommended to improve vocabulary acquisition and student engagement.